A Highly Efficient Xylan-Utilization System in Aspergillus niger An76: A Functional-Proteomics Study - Gong, Weili; Dai, Lin; Zhang, Huaiqiang; Zhang, Lili; Wang, Lushan (Frontiers in Microbiology, 2018)
Xylan constituted with β-1,4-D-xylose linked backbone and diverse substituted side-chains is the most abundant hemicellulose component of biomass, which can be completely and rapidly degraded into fermentable sugars by Aspergillus niger. This is of great value for obtaining renewable biofuels and biochemicals. To clarify the underlying mechanisms associated with highly efficient xylan degradation, assimilation, and metabolism by A. niger, we utilized functional proteomics to analyze the secreted proteins, sugar transporters and intracellular proteins of A. niger An76 grown on xylan-based substrates. Results demonstrated that the complete xylanolytic enzyme system required for xylan degradation and composed of diverse isozymes was secreted in a sequential order. Xylan-backbone-degrading enzymes were preferentially induced by xylose or other soluble sugars, which efficiently produced large amounts of xylooligosaccharides (XOS) and xylose; however, XOS was more efficient than xylose in triggering the expression of the key transcription activator XlnR, resulting in higher xylanase activity and shortening xylanase-production time. Moreover, the substituted XOS was responsible for improving the abundance of side-chain-degrading enzymes, specific transporters, and key reductases and dehydrogenases in the pentose catabolic pathway. Our findings indicated that industries might be able to improve the species and concentrations of xylan-degrading enzymes and shorten fermentation time by adding abundant intermediate products of natural xylan (XOS) to cultures of filamentous fungi.